نمذجة ومحاكاة دارة تبريد امتصاصية بمرحلة واحدة باستخدام برنامج TRNSYS - نبهان خياطة; عامر حاج طالب; محمد عتابـة (Tishreen University, 2019)
يتزايد الطلب على الطاقة الكهربائية بشكلٍ كبير خلال الصيف نتيجة الاستخدام الواسع لأنظمة تكييف الهواء. من ناحية أخرى تُحدث وسائط التبريد الهيدروكربونية المستخدمة في الأنظمة الانضغاطية التقليدية أضراراً كبيرة على طبقة الأوزون الجوية. لهذا فإن استخدام دارات التبريد الامتصاصية التي تستخدم الطاقة الحرارية (الشمسية أو الجيوحرارية أو أي مصدر حراري أخر) يُعدُّ أمراً مهماً في مجال التقليل من الاعتماد على الطاقة الكهربائية في أوقات الذروة والتخفيف من التلوث البيئي. يقدم هذا البحث نمذجة ومحاكاة لدارة تبريد امتصاصية بمرحلة واحدة وتستخدم محلول بروميد الليثيوم ماء كزوج عامل. تم توظيف معادلات انتقال الحرارة والكتلة ومعادلات تصف خواص الموائع العاملة في برمجة وتطوير برنامج TRNSYS من خلال إضافة عنصر Type210 إلى مكتبة البرنامج بهدف تشكيل نموذجٍ للدارة وتحليل الحساسية. تمت دراسة تأثير تغيرات درجات حرارة المبخر والمولد ودرجات تركيز المحلول وفعالية المبادل الحراري والأحمال الحرارية على معامل أداء الدارة. أظهرت النتائج التأثير الواضح للمبادل الحراري في تحسين معامل الأداء، كما أظهرت مقارنة نتائج المحاكاة بالنتائج التجريبية تقارباً كبيرًا. During the summer, the demand for electricity greatly increases because of the extensive use of the Air-conditioning systems. On the other hand, vapor compression systems have many impacts on stratospheric ozone depletion because of the (CFC) and (HCFC) refrigerants. Absorption Refrigeration Cycles powered by solar, geothermal or any thermal energy source becomes attractive to reduce the dependence on electricity in the periods of peak and to attenuate the environmental pollution. This study presents modeling and simulation of a single stage water/Lithium Bromide absorption refrigeration cycle. The adequate equations of heat and mass transfer, and appropriate equations describing the properties of working fluids are specified and employed in developing and programming the TRNSYS program. A new type (type210) was added to the TRNSYS library enabling users to complete modeling and sensitivity analysis of ARC. The performance coefficient of the cycle related to generator, evaporator temperatures, percentage ratio of LiBr solution, solution heat exchanger efficiency and thermal loads are all examined. As a result, it is found that the solution heat exchanger has a distinct effect in increasing the coefficient of performance. The simulation results are compared with the practical experiments, and it was satisfied.